차기 국가수준 체육과 교육과정 개발에 필요한 쟁점 - 윤기준; Keejoon Yoon (Ch'eyuk kwahak yŏn'gu, 2019)
[목적] 이 연구의 목적은 차기 국가수준 체육과 교육과정 개발 과정에서 논의되어야 할 쟁점 사항을 제시하는 데 있다. [방법] 2007 개정 체육과 교육과정, 2009 개정 교육과정에 따른 체육과 교육과정, 2015 개정체육과 교육과정 문서를 분석하였다. [결과] 첫째, 신체활동 가치와 교과 역량 간의 명확한 관계가 설정되어 있지 않다. 둘째, 신체활동 가치가 내용 영역으로 제시되고 있는 현재의 내용 체계표는 교과 역량의 층위 설정 및 역량 기반 체육수업 설계에 실질적인 도움을 제공하지 못한다. 셋째, 2015 개정 체육과 교육과정 문서는 명료성, 활용성, 가독성이 떨어진다. [결론] 연구 결과를 바탕으로 효과적인 국가 수준 체육과 교육과정 개발을 위한 후속 연구로 신체활동 가치와 교과 역량 간의 관계 설정과 내용 영역 구성 방안을 제안하였다. [Purpose] The purpose of this study is to suggest issues needed in the process of developing the next national physical education curriculum. [Methods] Data were collected from three different physical education curricula including the 2007 revised physical education curriculum, the 2011 physical education curriculum based on the 2009 revised curriculum and the 2015 revised physical education curriculum. [Results] Three findings emerged. Firstly, there was no clear conceptual relationships between physical activity value and subject competency. Secondly, the way in which physical activity value works as learning content area cannot offer helps to set the level of subject competency and to design physical education lessons that based on the subject competency. Lastly, the 2015 revised physical education curriculum has low level of clarity, usability and readability. [Conclusions] This study suggests the three different findings as issues that should be discussed in the development of the next physical education curriculum.